Influence of preservation methods on the quality of colostrum sourced from New Zealand dairy farms. Issue 5 (3rd September 2017) - Denholm, KS; Hunnam, JC; Cuttance, EL; McDougall, S
Abstract: AIMS: To assess the effect of two temperatures (ambient temperature and 4°C), three preservation methods (no preservative, yoghurt and potassium sorbate), and two periods of storage (3 and 7 days) on Brix and total bacterial and coliform counts of colostrum collected from New Zealand dairy farms. METHODS: One litre of colostrum destined to be fed to newborn calves was collected from 55 New Zealand dairy farms in the spring of 2015. Six aliquots of 150 mL were obtained from each colostrum sample, with two aliquots left untreated, two treated with potassium sorbate and two with yoghurt, and one of each pair of aliquots stored at ambient temperature and the other at 4°C. All samples were tested for Brix, total bacterial counts and coliform counts before treatment (Day 0), and after 3 and 7 days of storage. The effect of preservation method and storage temperature on the change in Brix, bacterial and coliform counts after 3 or 7 days of storage was analysed using multivariable random effects models. RESULTS: For all outcome variables there was a temperature by preservation interaction. For aliquots preserved with potassium sorbate, changes in Brix and bacterial counts did not differ between aliquots stored at ambient temperature or 4°C, but for aliquots preserved with yoghurt or no preservative the decrease in Brix and increase in bacterial counts was greater for aliquots stored at ambient temperature than 4°C (p<0.001). For aliquots preserved with potassium sorbate, coliform counts decreased at both temperatures, but for aliquots preserved with yoghurt or no preservative coliform counts increased for aliquots stored at 4°C, but generally decreased at ambient temperatures (p<0.001). There was also an interaction between duration of storage and temperature for bacterial counts (p<0.001). The difference in the increase in bacterial counts between aliquots stored at 4°C and ambient temperature after 3 days was greater than between aliquots stored at 4°C and ambient temperature after 7 days. CONCLUSIONS AND CLINICAL RELEVANCE: Use of potassium sorbate to preserve colostrum for 3 or 7 days resulted in little or no reduction in Brix and a lower increase in total bacterial counts than colostrum stored without preservative or with yoghurt added. Colostrum quality was not affected by storage temperature for samples preserved with potassium sorbate, but storage at 4°C resulted in better quality colostrum than storage at ambient temperatures for colostrum with no preservative or yoghurt added.